2001
DOI: 10.1091/mbc.12.6.1819
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin-enriched Microdomains at the Golgi Complex

Abstract: Sphingomyelin- and cholesterol-enriched microdomains can be isolated as detergent-resistant membranes from total cell extracts (total-DRM). It is generally believed that this total-DRM represents microdomains of the plasma membrane. Here we describe the purification and detailed characterization of microdomains from Golgi membranes. These Golgi-derived detergent-insoluble complexes (GICs) have a low buoyant density and are highly enriched in lipids, containing 25% of total Golgi phospholipids including 67% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
134
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 84 publications
20
134
1
1
Order By: Relevance
“…This article clearly demonstrates that DRMs can be isolated from the GA of plant cells, a result in line with the presence of lipid microdomains in the GA of animal cells (Hansen et al, 2000;Gkantiragas et al, 2001) and yeast (Bagnat et al, 2000). However, although the presence of lipid microdomains in the ER of animal cells (Sevlever et al, 1999) and yeast (Bagnat et al, 2000;Lee et al, 2002) has been reported, our attempts to isolate significant amounts of DRMs from the ER of leek cells were unsuccessful.…”
Section: Discussionsupporting
confidence: 75%
“…This article clearly demonstrates that DRMs can be isolated from the GA of plant cells, a result in line with the presence of lipid microdomains in the GA of animal cells (Hansen et al, 2000;Gkantiragas et al, 2001) and yeast (Bagnat et al, 2000). However, although the presence of lipid microdomains in the ER of animal cells (Sevlever et al, 1999) and yeast (Bagnat et al, 2000;Lee et al, 2002) has been reported, our attempts to isolate significant amounts of DRMs from the ER of leek cells were unsuccessful.…”
Section: Discussionsupporting
confidence: 75%
“…We considered the possibility that a change in cholesterol levels might affect the function of microdomains at the Golgi complex. Recently we obtained evidence for the existence of such microdomains at the early Golgi complex (30). We now show that changing the cholesterol content of membranes specifically affects the phase partitioning of heterotrimeric G proteins, suggesting a possible involvement of microdomains in the regulation of protein transport through the Golgi apparatus.…”
mentioning
confidence: 59%
“…Golgi-derived microdomains can be isolated as detergent-resistant membranes, enriched in sphingolipids and cholesterol (30). To determine the amount of cholesterol that partitions in microdomains, Triton X-100 was added to solubilize Golgi membranes.…”
Section: Cholesterol Affects Transport Within the Golgi Complex-mentioning
confidence: 99%
“…Extensive evidence in various organelles and processes (especially the TGN; endocytosis; constitutive exocytosis) has demonstrated the key role of rafts in membrane dynamics (fusions, fissions, trafficking, and interactions: for reviews, see Nichols, 2003;Helms and Zurzolo, 2004;Mayor and Rao, 2004). The abundance of rafts, as observed in enlargeosomes, is not common among the organelles competent for regulated exocytosis and could therefore play specific roles at various steps of the new vesicle life, including (in addition to exocytosis, which is discussed below): generation, presumably at specific domain(s) of the TGN (Gkantiragas et al, 2001;Maxfield, 2002;Gleeson et al, 2004); traffic and possible interactions, homologous and possibly also heterologous with other membrane systems. The recognition of the extensive detergent resistance, the first general property of the enlargeosome membrane so far identified, could serve in the study of these processes, for example, by providing criteria for the isolation and characterization of the vesicles together with important cues and tools for the interpretation of future results.…”
Section: Discussionmentioning
confidence: 99%